A high-protein diet with and without strength training shows no negative effects on oxidative stress markers in older adults - Laura Bragagna; Lina Maqboul; Ricarda Baron; Muriel Harloff; Monika Spasova; Sahar Noori; Agnes Draxler; Bernhard Franzke; Eva-Maria Strasser; Patrick A. Zöhrer; Sandra Unterberger; Rudolf Aschauer; et al. (Redox Biology)
A long, healthy and pain-free life is the goal of an aging society. However, people become increasingly less active in old age, which can lead to sarcopenia. To counteract this development, strength training and a sufficient protein supply are essential. To investigate the effects of a high-protein diet in combination with strength training on oxidative stress markers in older adults, 116 men and women underwent a 17-week single-blind randomized control trial with 3 groups (Control CON, Recommended Protein RP and High Protein HP) as part of the NutriAging Study.After finishing a 6-week dietary intervention, a strength training program was additionally implemented for RP and HP for the remaining study period. CON continued with their habitual protein intake throughout the study. Blood was drawn at three time points (baseline T1, week 8 T2, and after study completion T3) and analyzed for chemical blood parameters and the oxidative stress markers superoxide dismutase (SOD), glutathione-peroxidase (GSH-Px), catalase (CAT), ferric reducing ability potential (FRAP); γ-glutamyl-cysteinyl-glycine (GSH), glutathione disulfide (GSSG), unconjugated bilirubin (UCB), and malondialdehyde (MDA). The results showed a significant time effect of certain blood parameters and all measured oxidative stress markers independent of group allocation. This can be explained by seasonal changes over the study period. Urea and blood urea nitrogen (BUN) were significantly increased in HP, which could be attributed to the high protein intake, however they remained in the normal range. UCB and FRAP were significantly lower in HP, which could be due to the metabolization of the additional protein. Women in particular showed more altered oxidative stress markers as well as reduced uric acid (UA) in the HP group, suggesting lower estrogen secretion during menopause, possibly due to decreased nuclear factor erythroid 2-related factor 2 (NrF2) synthesis and subsequently impaired antioxidant defense. The strength training intervention alone showed no negative effects on blood or oxidative stress parameters. In summary, a high-protein diet along with strength training showed no major impact on oxidative stress in older adults.